The Effect of Current Ratio (Cr), Debt To Equity Ratio (Der), and Net Profit Margin (Npm) on Stock Returns in Manufacturing Companies in the Trade, Services, and Investment Sector on the Indonesia Stock Exchange in the 2017-2020 Period - Jordy Anderson; Stephen Audi Giordani; Shellen Kangnata; Dhea Francisca (Institute of Computer Science (IOCS), 2021)
The purpose of this research is to examine how the influence of Current Ratio, Debt To Equity Ratio, and Net Profit Margin on Stock Return, either partially or simultaneously. This research includes descriptive researchquantitative. Population 154 companies are manufacturing companies in the trade, services and investment sectors on the IDX and the sample studied is 17 companies for 4 periods. The statistical method is multiple linear regression analysis. The results show that the classical assumptions have met the requirements. Partially (t test), Current Ratio and Debt To Equity Ratio have an influence on Stock Return. Simultaneously (F test) Current Ratio, Debt To Equity Ratio, and Net Profit Margin have no and no significant effect on Stock Return. The magnitude of the coefficient of determination is 6.6% while the remaining 93.5% Stock Return can be explained by other factors.